11Beta‐hydroxysteroid dehydrogenase‐1 deficiency or inhibition enhances hepatic myofibroblast activation in murine liver fibrosis. Issue 6 (22nd February 2018) - Zou, Xiantong; Ramachandran, Prakash; Kendall, Timothy J.; Pellicoro, Antonella; Dora, Elena; Aucott, Rebecca L.; Manwani, Kajal; Man, Tak Yung; Chapman, Karen E.; Henderson, Neil C.; Forbes, Stuart J.; Webster, Scott P.; et al.
Abstract : A hallmark of chronic liver injury is fibrosis, with accumulation of extracellular matrix orchestrated by activated hepatic stellate cells (HSCs). Glucocorticoids limit HSC activation in vitro, and tissue glucocorticoid levels are amplified by 11beta‐hydroxysteroid dehydrogenase‐1 (11βHSD1). Although 11βHSD1 inhibitors have been developed for type 2 diabetes mellitus and improve diet‐induced fatty liver in various mouse models, effects on the progression and/or resolution of liver injury and consequent fibrosis have not been characterized. We have used the reversible carbon tetrachloride‐induced model of hepatocyte injury and liver fibrosis to show that in two models of genetic 11βHSD1 deficiency (global, Hsd11b1 –/–, and hepatic myofibroblast‐specific, Hsd11b1 fl/fl /Pdgfrb‐cre) 11βHSD1 pharmacological inhibition in vivo exacerbates hepatic myofibroblast activation and liver fibrosis. In contrast, liver injury and fibrosis in hepatocyte‐specific Hsd11b1 fl/fl /albumin‐cre mice did not differ from that of controls, ruling out 11βHSD1 deficiency in hepatocytes as the cause of the increased fibrosis. In primary HSC culture, glucocorticoids inhibited expression of the key profibrotic genes Acta2 and Col1α1, an effect attenuated by the 11βHSD1 inhibitor [4‐(2‐chlorophenyl‐4‐fluoro‐1‐piperidinyl][5‐(1H‐pyrazol‐4‐yl)‐3‐thienyl]‐methanone. HSCs from Hsd11b1 –/– and Hsd11b1 fl/fl /Pdgfrb‐cre mice expressed higher levels of Acta2 and Col1α1 and were correspondingly more potently activated. In vivo [4‐(2‐chlorophenyl‐4‐fluoro‐1‐piperidinyl][5‐(1H‐pyrazol‐4‐yl)‐3‐thienyl]‐methanone administration prior to chemical injury recapitulated findings in Hsd11b1 –/– mice, including greater fibrosis. Conclusion: 11βHSD1 deficiency enhances myofibroblast activation and promotes initial fibrosis following chemical liver injury; hence, the effects of 11βHSD1 inhibitors on liver injury and repair are likely to be context‐dependent and deserve careful scrutiny as these compounds are developed for chronic diseases including metabolic syndrome and dementia. (Hepatology 2018;67:2167‐2181).